2011
DOI: 10.1101/gad.2045111
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a CENP-A–histone H4 heterodimer in complex with chaperone HJURP

Abstract: In higher eukaryotes, the centromere is epigenetically specified by the histone H3 variant Centromere Protein-A (CENP-A). Deposition of CENP-A to the centromere requires histone chaperone HJURP (Holliday junction recognition protein). The crystal structure of an HJURP-CENP-A-histone H4 complex shows that HJURP binds a CENP-A-H4 heterodimer. The C-terminal b-sheet domain of HJURP caps the DNA-binding region of the histone heterodimer, preventing it from spontaneous association with DNA. Our analysis also reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
228
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(251 citation statements)
references
References 30 publications
19
228
1
Order By: Relevance
“…In vivo , the assembly process is catalyzed by histone chaperones, a diverse class of proteins that is involved in histone turnover including transport, transfer, and storage (De Koning et al , 2007). Structural studies of histone chaperones bound to cognate histones have revealed that histone chaperones frequently protect hydrophobic histone interfaces that become solvent‐exposed outside of the context of the nucleosome or neutralize excess positive charge by providing an acidic binding pocket to directly compete with non‐specific electrostatic histone–DNA interactions (English et al , 2006; Zhou et al , 2008, 2011; Cho & Harrison, 2011; Hu et al , 2011; Elsasser et al , 2012; Liu et al , 2012; Hondele et al , 2013; Obri et al , 2014; Huang et al , 2015). However, how chaperones mediate the final deposition onto DNA to assemble nucleosomes remains poorly understood (Loyola & Almouzni, 2004; De Koning et al , 2007; Elsasser & D'Arcy, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In vivo , the assembly process is catalyzed by histone chaperones, a diverse class of proteins that is involved in histone turnover including transport, transfer, and storage (De Koning et al , 2007). Structural studies of histone chaperones bound to cognate histones have revealed that histone chaperones frequently protect hydrophobic histone interfaces that become solvent‐exposed outside of the context of the nucleosome or neutralize excess positive charge by providing an acidic binding pocket to directly compete with non‐specific electrostatic histone–DNA interactions (English et al , 2006; Zhou et al , 2008, 2011; Cho & Harrison, 2011; Hu et al , 2011; Elsasser et al , 2012; Liu et al , 2012; Hondele et al , 2013; Obri et al , 2014; Huang et al , 2015). However, how chaperones mediate the final deposition onto DNA to assemble nucleosomes remains poorly understood (Loyola & Almouzni, 2004; De Koning et al , 2007; Elsasser & D'Arcy, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…HJURP (Holliday junction recognition protein) was originally named because it was suggested to bind Holliday junctions (Kato et al 2007) and was subsequently identified in purifications of soluble CENP-A complexes that represent a prechromatin assembly intermediate Foltz et al 2009). HJURP and Scm3 bind directly to a dimer of CENP-A and histone H4 through recognition of the CATD domain of CENP-A by HJURP/Scm3's conserved amino terminus (Foltz et al 2009;Shuaib et al 2010;Cho and Harrison 2011;Hu et al 2011;Zhou et al 2011). In addition, HJURP forms contacts with CENP-A outside of the CATD that enhance the stability of the HJURP:CENP-A:H4 complex (Bassett et al 2012).…”
Section: Hjurp: the Cenp-a Chaperonementioning
confidence: 99%
“…The CATD region of CENP-A is also important for direct recruitment and binding of CENP-N. Furthermore, this region specifically binds to the Scm3 domain of HJURP 17,40 . It is clear from this data the CATD region in human cells is highly important in being recruited to and identifying the site for centromere assembly.…”
Section: Cenp-a Structural Characteristicsmentioning
confidence: 99%
“…The β-sheet of HJURP/Scm3 interacts along the positively charged groove of CENP-A/Cse4 that is necessary for DNA binding. Thus, HJURP/Scm3 also functions to preclude CENP-A/Cse4 form binding DNA prematurely 40,75,76 . As stated above, previous work in our lab has found HJURP has a C-terminal self dimerization domain, this domain is thought to allow the two heterotrimeric HJURP-CENP/H4 complexes to localize to centromeres in conjunction with one another, thereby allowing for octameric nucleosome assembly 74 .…”
Section: Centromere Priming Components: Hjurpmentioning
confidence: 99%
See 1 more Smart Citation